Long‐term functional and oncological outcomes of nerve‐sparing and prostate capsule‐sparing cystectomy: a single‐centre experience. (12th July 2019) - Saad, Mohamed; Moschini, Marco; Stabile, Armando; Macek, Petr; Lanz, Camille; Prapotnich, Dominique; Rozet, Francois; Cathala, Nathalie; Mombet, Annick; Sanchez‐Salas, Rafael; Cathelineau, Xavier
Abstract : Objectives: To evaluate the technical feasibility, oncological and functional outcomes of nerve sparing cystoprostatectomy (NSCP) and prostate capsule‐sparing cystectomy (PCSC) for the treatment of organ‐confined bladder cancer at a single referral centre. Patients and Methods: From April 2001 to June 2012, 60 patients underwent PCSC and 47 were treated with NSCP. Inclusion criteria for PCSC were: fully informed consent for the well‐motivated patient; negative transurethral resection of the bladder neck; normal prostatic specific antigen (PSA) level (defined as <4 ng/dL during the first year of the study, which was later lowered to 2.5 ng/dL); and normal transrectal ultrasonography, with biopsy for any suspicious nodule. Patients received a complete oncological and functional follow‐up. The Kaplan–Meier method was used to depict survival outcomes after surgery. Results: After a median follow‐up of 73 and 62 months for PCSC and NSCP, respectively, the 5‐year cancer‐specific survival was 90% for the PCSC group and 78% for the NSCP group ( P  = 0.055). Considering complications within 30 days after surgery, 13% and 21% patients had Clavien ≥III complications in the PCSC and NSCP groups, respectively ( P  = 0.2). For functional outcomes, at 3 months after surgery, 54 (90%) and 24 (51%) patients reported full recovery of daytime urinary continence in the PCSC and NSCP groups, respectively ( P  < 0.001); and for erectile function recovery, 32 (53%) and four (9%) patients in the PCSC group and in the NSCP group were respectively potent without any treatment ( P  < 0.001). Conclusions: NSCP and PCSC are appropriate for a subset of patients with bladder cancer, with excellent oncological and functional results. These surgical procedures should be proposed to well‐motivated patients.